Formal [8+3]-Annulation between Azaoxyallyl Cations and Tropones - Force, Guillaume; Pérot, Amélie; Guillot, Régis; Gandon, Vincent; Leboeuf, David (Synthesis, 2020)
For the first time, azaoxyallyl cations were used as cycloaddition partners with tropone derivatives to access nitrogen-containing [7,6]-fused bicycles in a metal-free process under mild reaction conditions. DFT computations have been used to shed light on the selectivities observed during the course of the reaction.
Keywords: tropone; α-haloamide; azaoxyallyl cation; cycloaddition; DFT computations